Analysis of the Basics of Fatwa Gold Credit DSN-MUI Perspective of Qaidah Ushul Fiqh - Fajri Nur Setyawan (Demak Universal Journal of Islam and Sharia, 2023)
The MUI National Sharia Council has issued a fatwa allowing the sale and purchase of gold on credit. This fatwa at first glance contradicts the hadiths which contain the obligation to exchange gold for gold in cash. Until not a few Islamic economists in books or articles criticized the fatwa. One of them is Erwandi Tarmizi in his book entitled 'Harta Haram Muamalat Contemporary'. The author criticizes the fatwa and explains the weak sides of its argument. So this study aims to analyze the extent of the compatibility of the arguments of the MUI National Sharia Council with the rules of Ushul Fiqh related to Islamic economics. The method used is qualitative with a literature approach, and discriptive-qualitative, with a normative approach. The results showed that some of the arguments used by the MUI National Sharia Council that were considered strong were the propositions of the rules of Ushul Fiqh related to 'illat law and the rules of Fiqh related to 'urf. So the opinion of the MUI National Sharia Council in this matter has been in line with the rules of Ushul Fiqh in concluding a law from its propositions.